Gambaran Pengetahuan Siswa Tentang Gangguan Pola Tidur di MAN Model Palangka Raya: Description of Student Knowledge About Sleep Pattern Disorders in the MAN Model Palangka Raya - Mansyah, H. Barto; Supriandi, Supriandi; Berthiana, Berthiana; Mewo, Meity Kristien (Jurnal Surya Medika (JSM), 2023)
Sleep is a basic need for everyone so that the body can function normally after its daily activities. In adolescents there are changes in sleep patterns, including reduced sleep duration, delayed bedtime, and differences in sleep patterns on weekdays and weekends. Thus, the quality of adolescent sleep also tends to be reduced or disrupted. There are several serious consequences of sleep disturbances such as excessive daytime sleepiness, impaired attention and memory, depression, frequent falls, inappropriate use of hypnotics, and decreased quality of life. The purpose of this study was to determine the level of students' knowledge about sleep pattern disturbances at the Palangka Raya Model MAN in good, adequate and poor levels. This study uses a quantitative descriptive method. The population in this study were students at the Palangka Raya Model MAN in the 2020/2021 academic year. The sampling technique used was total sampling with a total sample of 90 respondents. The instrument used was a closed questionnaire. Based on the results of the study, it was obtained an overview of students' knowledge about sleep pattern disturbances in the good category of 78 people, the sufficient category of 12 people and no respondents in the less category. Based on the results of the study, it was shown that most of the students' knowledge of the Palangka Raya MAN Model regarding sleep disturbances was good, namely a number of 78 people. Suggestions for future researchers are to be able to develop this research so as to obtain varied research results.